Laurence A. Mound 90 years: A collaborative life that laid the foundation of modern thrips studies - Lima, Élison Fabrício B.; Tree, Desley J.; Wells, Alice; Cavalleri, Adriano (Zootaxa, 2024)
In honour of Laurence Mound’s 90th birthday, this special issue of Zootaxa serves as a tribute to his enduring legacy in entomology and Thysanoptera research. Mound’s journey in the field has been marked by numerous discoveries, unwavering dedication, and invaluable collaborations that have profoundly influenced the study of Thysanoptera around the world. We here emphasise his lifelong commitment to the study of these minute insects and this provides an opportunity for researchers worldwide to share their insights and experiences, highlighting the impact Mound has had on their scientific pursuits. Through an interview exploring Mound’s career choices, this paper also unravels the intricate paths he traversed and the collaborations that proved to be the driving force behind his Thysanoptera research to the age of 90.